Cutting Microfinance Interest Rates: An Opportunity Co‐Creation Perspective. (27th August 2014) - Sun, Sunny Li; Im, Junyon
<x xml:space="preserve">Abstract</x> Microfinance is a social innovation to alleviate poverty by providing small, unsecured loans to local indigent entrepreneurs. Many borrowers use microfinance loans to seed their small entrepreneurial businesses. However, high interest rates charged by microfinance institutions (MFIs) are likely to increase the financial burden of those borrowers. In this study, we adopt an opportunity co‐creation perspective to analyze the factors that affect microfinance interest rates. We argue that new opportunities in a social venture could be co‐created by multiple stakeholders, including MFIs, borrower communities, female borrowers, governments, MFI managers, and employees. We tested our hypothese on interest rate setting of MFIs by using 4, 187 organization‐year observations from 2003 to 2011 across 93 countries, and the empirical results largely support the hypotheses. Our opportunity co‐creation perspective extends the current understanding on microfinance and provides important managerial implications.